1997
DOI: 10.1152/ajplung.1997.272.1.l106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lowering serum cholesterol on the composition of surfactant in adult rat lung

Abstract: Treatment of rats with 10 mg.kg body wt-1 day-1 4-aminopyrazolo[3,4-d]pyrimidine (APP) for 2 days markedly reduced serum cholesterol and phospholipids. This was associated with large decreases in the principal component of alveolar surfactant, the disaturated phospholipids (DSP), in the lamellar body and in the tubular myelin-rich and -poor alveolar fractions, but with no concomitant change in cholesterol or surfactant protein A. These decreases in DSP were associated with a decrease in the synthesis of surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Furthermore, it has recently been demonstrated that mice fed a high cholesterol diet exhibit an increased level of serum cholesterol and that the surfactant obtained from these mice had increased cholesterol values with impaired biophysical function (24). However, Davidson et al (7) demonstrated that lowering levels of serum cholesterol by inhibiting the release of hepatic lipoproteins did not affect surfactant cholesterol levels, due to the ability of type II cells to synthesize cholesterol. These findings provide evidence that, at least in the uninjured lung, surfactant cholesterol arises from the serum and/or de novo synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has recently been demonstrated that mice fed a high cholesterol diet exhibit an increased level of serum cholesterol and that the surfactant obtained from these mice had increased cholesterol values with impaired biophysical function (24). However, Davidson et al (7) demonstrated that lowering levels of serum cholesterol by inhibiting the release of hepatic lipoproteins did not affect surfactant cholesterol levels, due to the ability of type II cells to synthesize cholesterol. These findings provide evidence that, at least in the uninjured lung, surfactant cholesterol arises from the serum and/or de novo synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable ability of the lung to maintain fairly normal cholesterol and phospholipid levels in the face of these conditions is impressive. It has been shown that depressing the hepatic secretion of all serum lipoproteins for 3 days with 4-aminopyrazolo(3,4d)pyrimidine results in a parallel reduction of phospholipids in both the surfactant and lamellar body fractions, whereas cholesterol content remains unaltered (15,58). However, despite the profound reduction in plasma phospholipid and cholesterol over the lifetime of the ABCA1Ϫ/Ϫ mouse, there was a moderate enrichment in phospholipid levels in lung tissue and a significant cholesterol enrichment accompanied by pathological alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar CHOL is purported to be derived primarily from serum lipoproteins via lamellar bodies (27). However, we have recently reported that lamellar bodies in fact contain little CHOL (12) and that CHOL and DPPC are handled independently (28). The role and source of CHOL in surfactant is unresolved.…”
Section: Cholesterolmentioning
confidence: 99%
“…Phospholipid classes were separated by high performance liquid chromatography (HPLC) ( Porasil Silica; Waters Millipore, Bedford, MA) as described by Pison and associates (11) and quantified using a mass detector (Model 750/14; Applied Chromatography System, Cheshire, UK) coupled to a Delta Chromatography Data System program (Digital Solutions, Margate, Australia), Sphingosine (Sigma Chemicals, St. Louis, MO) was included as an internal standard. Neutral lipids were separated by HPLC using a Waters 18 C Novapak column (Waters Millipore) and free cholesterol (CHOL) was quantified by its absorption at 210 nm (12).…”
Section: Surfactant Analysismentioning
confidence: 99%